A New Woke Religion: Are Universities to Blame? - Rosemary Sage (Ali Khorsandi Taskoh, 2022)
This article argues that in haste to define people as victims, from specific identities like race, a new woke religion is giving an interesting world a malign image. Higher Education (HE) promotes woke agendas that narrow debates and confine curricula content, by dismissing thinking and action that does not align with new identity policy and practice. This is the roar of "smug, entitled mediocrities", says Burchill (2021). The word woke is discussed and how HE uses it to limit opportunities, damage relationships and foster divisions with disastrous results. Woke-speak robs people of individuality and decency. Education, with a duty to fit students for life and work, should also have a role in developing personal awareness, responsibility and ideas of citizenship. To achieve this, governing systems need radical overhaul to minimise human divisions and improve life quality. HE must take a lead by promoting both instrumental and intrinsic values. In moral philosophy, these values are the distinction between what is a means to an end and what is an end in itself.